STUDENTS’ PERSPECTIVE ON “SPADA UMG” ONLINE LEARNING PLATFORM AT UNIVERSITY OF MUHAMMADIYAH GRESIK - ma’rifah, ulfatul; ardiyansah, tri yuli (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2022)
Online learning has great potential to provide students with meaningful learning experience. The use of online learning provided by university has a good impact for students in learning process. In University of Muhammadiyah Gresik, online learning has been applied as one of the teaching method. The university has its own online learning platform “SPADA UMG”. This research focused on analyzing the students’ perspective on SPADA UMG online learning platform. This research applied qualitative research design and used questionnaire and interview techniques. The result showed that the students’ responses on their perspective of SPADA UMG online learning varied into 4 indicators. They were; (1) learning needs; SPADA UMG helped students achieving their learning needs but also gave them difficulty to understand the material, (2) efficiency; taking course via SPADA UMG provided the students efficient condition to study anywhere and granted them additional time, (3) features; despite its imperfect features, SPADA UMG was easy for students to operate, and (4) access; students often got problem accessing SPADA UMG because of the server down or the internet connection. SPADA UMG also provided advantages such as its efficiency that granted students an efficient learning experience and convenience operating system. On the other hand, SPADA UMG also provided disadvantages such as problems to access the site and some error features